Common themes in early state policy responses to substance use disorder treatment during COVID-19. (4th July 2021) - Andraka-Christou, Barbara; Bouskill, Kathryn; Haffajee, Rebecca L.; Randall-Kosich, Olivia; Golan, Matthew; Totaram, Rachel; Gordon, Adam J.; Stein, Bradley D.
ABSTRACT: Background : Limited research has examined how states have changed policies for treatment of substance use disorder (SUD) during the COVID-19 pandemic. Objectives : We aimed to identify themes in state policy responses to the pandemic in the context of SUD treatment. Identifying themes in policy responses provides a framework for subsequent evaluations of the relationship between state policies and health service utilization. Methods : Between May and June 2020, we searched all Single State Agencies for Substance Abuse Services (SSA) websites for statements of SUD treatment policy responses to the pandemic. We conducted Iterative Categorization of policies for outpatient programs, opioid treatment programs, and other treatment settings to identify themes in policy responses. Results : We collected 220 documents from SSA websites from 45 states and Washington D.C. Eight specific themes emerged from our content analysis: delivery of pharmacological and non-pharmacological services, obtaining informed consent and documentation for remote services, conducting health assessments, facility operating procedures and staffing requirements, and permissible telehealth technology and billing protocols. Policy changes often mirrored federal guidance, for instance, by expanding methadone take-home options for opioid treatment programs. The extent and nature of policy changes varied across jurisdictions, including telehealth technology requirements and staffing flexibility. Conclusion : States have made significant policy changes to SUD treatment policies during COVID-19, particularly regarding telehealth and facilitation of remote care. Understanding these changes could help policymakers prioritize guidance during the pandemic and for future health crises. Impacts of policies on disparate treatment populations, including those with limited technological access, should be considered.